Comparison of Physical Activity of Generation Z and Millennial Running Participants in Sports Tourism - Syahvira; Yudy Hendrayana; Sucipto (Journal of Physical Education Health and Sport, 2026)
Mass running events have emerged as an increasingly popular lifestyle trend among different age groups, connecting sport and recreation with public health. In this study, the researcher wants to evaluate and compare the physical activity of Gen Z and Gen Y (Millennials) who run sport tourism in Bandung city, West Java. Comparative descriptions were used to evaluate the behaviors of these two cohorts, and the methods used were descriptive. Out of the 100 non-athletes that participated in the research, 50 were Millennials and 50 were Generation Z participants. The International Physical Activity Questionnaire Short Form was used to determine the amount of energy expended in MET-minutes/week. The data analysis was descriptive statistics, crosstabulation and Mann-Whitney U test which were selected due to the results of prerequisite evaluation that showed the data were not normally distributed and not homogeneous. The descriptive data revealed that, mean physical activity score for Generation Z is 2439.30 MET-minutes/weeks which is slightly higher than that of Millennials (2356.86 MET-minutes/weeks). Moreover, 22.0 per cent of participants in Generation Z had high activity levels, while 14.0 per cent of participants in the Millennials category had high activity levels, but the majority of response categories were classified into the moderate activity category. The Mann-Whitney U test, however, found an asymptotic significance value of 0.129. This figure is less than 0.05, which suggests that the overall physical activity levels are not measurably different between the two generations. The study finds that sport tourism is a lifestyle factor that brings people together regardless of age. Generation Z and Millennials exhibit similar active behaviours, which means mass running events are a successful initiative for public health and whole-of-person wellness, transcending the generational divide.